THE EFFECT OF EARNING PER SHARE (EPS), RETURN ON EQUITY (ROE) AND NET PROFIT MARGIN (NPM) ON SHARE RETURN OF CEMENT SUB-SECTOR COMPANIES LISTED ON THE IDX - Riska; Ramli, Anwar; Anwar; Nurman; Amin, Andi Mustika (Journal Management & Economics Review (JUMPER), 2023)
This study aims to determine the effect of Earning Per Share (EPS), Return On Equity (ROE), and Net Profit Margin (NPM) on Stock Returns of Cement Sub Sector Companies Registered on the IDX. This type of research is descriptive quantitative. This study uses independent variables, namely Earning Per Share (EPS), Return On Equity (ROE), and Net Profit Margin (NPM). The dependent variable is Stock Return. The data used is secondary data derived from the financial reports of cement sub-sector companies listed on the IDX in 2017-2022. The research sample was taken by purposive sampling method, so that 6 companies were obtained that met the criteria. The research data were analyzed using SPSS version 26. The results of the analysis show that partially the EPS variable has a positive and significant effect on stock returns. While the ROE and NPM variables have no significant effect on stock returns. And simultaneously the variables EPS, ROE, and NPM have no significant effect on stock returns. The results of the Adjusted R Square analysis are 0.102 which indicates that EPS, ROE, and NPM are only able to contribute to Return Shaam of 10.2%, the remaining 89.8% are influenced by other factors not examined.